Pengoptimalan Pengambilan Keputusan Perusahaan melalui Sistem Informasi Manajemen Berbasis Komputer - Mintawati, Hesri; Simangunsong, Bonse Aris Mandala Putra; Suhardi, Mulyadi; Fauzan, Fawwar; Sari, Putri Puspita; Maskanah, Siti Neng (Neolectura, 2023)
The use of computer-based Management Information Systems (MIS) has become crucial in corporate decision-making in this digital era. This study investigates the impact of computer- based MIS on the efficiency and quality of corporate decision-making. Through comprehensive literature analysis, it is found that MIS provides significant benefits in delivering quick and accurate information access, as well as aiding in overcoming the data overload issues that often hinder decision-making processes. The integration of cutting-edge technologies, such as predictive analytics and artificial intelligence, further strengthens the role of MIS in enhancing corporate decision-making responsiveness and intelligence. Thus, the development and implementation of computer-based MIS are crucial in improving performance and competitiveness in an increasingly competitive market.